Associação entre alterações circadianas do ECG Holter e morte súbita cardíaca em pacientes com cardiopatia chagásica - Alberto, Alex Chaves (2019)
Sudden cardiac death (SCD) is the leading cause of mortality throughout the various phases of Chagas’ disease, accounting for 55-65% of deaths. This study aims at determining a model that associates the circadian alterations of 24 h Holter and SCD in patients with chronic Chagas’ cardiopathy (CCC) with cardiac involvement. The studied sample comprised 82 CCC patients of both sexes, including 22 outcomes of SCD. Based on heart rate variability (HRV) and heart rate turbulence (HRT) analyses, various parameters were estimated for the period of 24 h and 12 h segments (day and night). Due to the imbalance between the number of alive and SCD patients, a supersampling approach was adopted, by considering three times each SCD case to avoid bias in the results. The forward stepwise multivariate analysis was applied to identify the variables that have better association with the clinical outcome. From a set of models, k nearest neighbors one presented the highest accuracy indices, 68% and 76% for the 24 h and the 12 h periods, respectively. The best performance was obtained in the 12 h analysis, using three variables from the nocturnal period, including one classical index from HRV (pNN50) and the two indices from HRT (turbulence onset and turbulence slope). The study allows to conclude that variables characterizing the parasympathetic autonomic control of the heart (pNN50) and the HRT phenomena during the night were independently associated with MSC in Chagas’ patients.